Fluoride and arsenic exposure impairs learning and memory and decreases mGluR5 expression in the hippocampus and cortex in rats. - Shoufang Jiang (PLoS ONE, 2014)
Fluoride and arsenic are two common inorganic contaminants in drinking water that are associated with impairment in child development and retarded intelligence. The present study was conducted to explore the effects on spatial learning, memory, glutamate levels, and group I metabotropic glutamate receptors (mGluRs) expression in the hippocampus and cortex after subchronic exposure to fluoride, arsenic, and a fluoride and arsenic combination in rats. Weaned male Sprague-Dawley rats were assigned to four groups. The control rats drank tap water. Rats in the three exposure groups drank water with sodium fluoride (120 mg/L), sodium arsenite (70 mg/L), and a sodium fluoride (120 mg/L) and sodium arsenite (70 mg/L) combination for 3 months. Spatial learning and memory was measured in Morris water maze. mGluR1 and mGluR5 mRNA and protein expression in the hippocampus and cortex was detected using RT-PCR and Western blot, respectively. Compared with controls, learning and memory ability declined in rats that were exposed to fluoride and arsenic both alone and combined. Combined fluoride and arsenic exposure did not have a more pronounced effect on spatial learning and memory compared with arsenic and fluoride exposure alone. Compared with controls, glutamate levels decreased in the hippocampus and cortex of rats exposed to fluoride and combined fluoride and arsenic, and in cortex of arsenic-exposed rats. mGluR5 mRNA and protein expressions in the hippocampus and mGluR5 protein expression in the cortex decreased in rats exposed to arsenic alone. Interestingly, compared with fluoride and arsenic exposure alone, fluoride and arsenic combination decreased mGluR5 mRNA expression in the cortex and protein expression in the hippocampus, suggesting a synergistic effect of fluoride and arsenic. These data indicate that fluoride and arsenic, either alone or combined, can decrease learning and memory ability in rats. The mechanism may be associated with changes of glutamate level and mGluR5 expression in cortex and hippocampus.